(untitled) (Nigerian Journal of Physiological Sciences, 2021)
Summary: The antihypertensive effect of Hibiscus sabdariffa (HS) has been validated in animals and man. This study tested the hypothesis that its hypotensive effect may be sympathetically mediated. The cold pressor test (CPT) and handgrip exercise (HGE) were performed in 20 healthy subjects before and after the oral administration of 15mg/Kg HS. The blood pressure (BP) and heart rate (HR) responses were measured digitally. Mean arterial pressure (MAP; taken as representative BP) was calculated. Results are expressed as mean ±SEM. P<0.05 was considered significant. CPT without HS resulted in a significant rise in MAP and HR (111.1±2.1mmHg and 100.8±2.0/min) from the basal values (97.9±1.9mmHg and 87.8±2.1/min; P<0.0001 respectively). In the presence of HS, CPT-induced changes (ΔMAP=10.1±1.7mmHg; ΔHR= 8.4±1.0/min) were significantly reduced compared to its absence (ΔMAP= 13.2±1.2mmHg; ΔHR= 13.8±1.6/min; P<0.0001 respectively). The HGE done without HS also resulted in an increase in MAP and HR (116.3±2.1mmHg and 78.4±1.2/min) from the basal values (94.8±1.6mmHg and 76.1±1.0/min; p<0.0001 respectively). In the presence of HS the HGE-induced changes (ΔMAP= 11.5±1.0mmHg; ΔHR= 3.3±1.0/min) were significantly decreased compared to its absence (ΔMAP=21.4±1.2mmHg; ΔHR= 12.8±2.0/min; P<0.0001 respectively). The CPT and HGE -induced increases in BP and HR suggest Sympathetic nervous system activation. These increases were significantly dampened by HS suggesting, indirectly, that its hypotensive effect may be due to an attenuation of the discharge of the sympathetic nervous system.